2020
DOI: 10.21203/rs.3.rs-15772/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fertility intentions and the way they change following birth- a prospective longitudinal study

Abstract: Introduction: Women's fertility intentions, their desired number of children and desired inter-pregnancy interval (IPI) are related to micro (personal) and macro (socio-cultural) level factors. We investigated factors that contribute to changes in women's fertility intentions in Israel, a developed country with high birth rates. Methods: Pregnant women (N=1163), recruited from prenatal clinics and hospitals in two major metropolitan areas, completed self-report questionnaires prenatally (≥24 weeks gestation) a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…The result of the adjusted model showed that compared to young women [15][16][17][18][19][20][21][22][23][24], women who desire no more children aged 25-34 [aOR = 1.85, 95% CI = 1. 44-2.38] and older than 35 years [aOR = 1.84, 95% CI = 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The result of the adjusted model showed that compared to young women [15][16][17][18][19][20][21][22][23][24], women who desire no more children aged 25-34 [aOR = 1.85, 95% CI = 1. 44-2.38] and older than 35 years [aOR = 1.84, 95% CI = 1.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the association between family planning use and high fertility rates [8,14], it is imperative to examine its predictors among women who desire no more children in SSA countries with high fertility rates. Indeed, the use of LARC/PMs affords women the opportunity to make an informed decision to choose whether to limit or space childbearing [15,16]. This is important because, in SSA, high fertility clusters cut across different spatially close countries, suggesting that focusing on country-specific family planning needs may not accurately reflect the disparities and variations in access to contraceptives in the region [11].…”
Section: Introductionmentioning
confidence: 99%